Researches of selected electric properties of threonine doped TGS single crystals - Proszak, Wladysław (Видавництво Національного університету "Львівська політехніка", 2002)
This paper contains results of the researches upon new pyroelectric material: triglycine sulphate doped with threonine. Because of the future application of the new obtained single crystal as the active element of IR detection, temperature characteristics of electric hysteresis loop parameters and pyroelectric coefficient were investigated. Temperature dependencies of spontaneous polarisation, coercive field and pyroelectric coefficient are presented as well as the measurement systems designed for determination of the mentioned above dependencies.
Keywords: TGS; single crystal; ferroelectrics; electric properties; pyroelectric effect; threonine